Electronic medical record implementation for a healthcare system caring for homeless people. Issue 1 (16th November 2018) - Angoff, Gerald H; O'Connell, James J; Gaeta, Jessie M; De Las Nueces, Denise; Lawrence, Michael; Nembang, Sanju; Baggett, Travis P
Abstract: Objective: Electronic medical record (EMR) implementation at centers caring for homeless people is constrained by limited resources and the increased disease burden of the patient population. Few informatics articles address this issue. This report describes Boston Health Care for the Homeless Program's migration to new EMR software without loss of unique care elements and processes. Materials and methods: Workflows for clinical and operational functions were analyzed and modeled, focusing particularly on resource constraints and comorbidities. Workflows were optimized, standardized, and validated before go-live by user groups who provided design input. Software tools were configured to support optimized workflows. Customization was minimal. Training used the optimized configuration in a live training environment allowing users to learn and use the software before go-live. Results: Implementation was rapidly accomplished over 6 months. Productivity was reduced at most minimally over the initial 3 months. During the first full year, quality indicator levels were maintained. Keys to success were completing before go-live workflow analysis, workflow mapping, building of documentation templates, creation of screen shot guides, role-based phased training, and standardization of processes. Change management strategies were valuable. The early availability of a configured training environment was essential. With this methodology, the software tools were chosen and workflows optimized that addressed the challenges unique to caring for homeless people. Conclusions: Successful implementation of an EMR to care for homeless people was achieved through detailed workflow analysis, optimizing and standardizing workflows, configuring software, and initiating training all well before go-live. This approach was particularly suitable for a homeless population.